PENGEMBANGAN INSTRUMEN PENILAIAN DENGAN APLIKASI QUIZIZZ PAPERMODE PADA PEMBELAJARA IPAS KEKAYAAN ALAM BAGI SISWA KELAS IV SD N TRANSABANGDEP - Elza Putri Purnamasari; Bunda Harini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an assessment instrument product based on the Quizizz PaperMode application for IPAS (Science and Social Studies Integration) learning on the topic of natural resources, intended for fourth-grade students at SD Negeri Transabangdep. The development of this instrument refers to the 3D development model, which consists of three main stages: Define, Design, and Development. Each stage was carried out systematically to ensure that the resulting product is relevant, effective, and aligned with the learning needs.To evaluate the feasibility of the product, a validation process was conducted by four validators, including a subject matter expert, a language expert, and a media expert. The validation results showed an average score of 91.6%, which falls into the category of highly valid and feasible for use in the learning process. Following the validation, a practicality test was also conducted by distributing questionnaires to 20 students in class IV A. Based on the results, a total score of 189 out of a maximum of 200 points was obtained, indicating an average practicality rate of 94.5%. This result suggests that the product is very easy to use and well-received by students.Based on the validation and practicality test results, it can be concluded that the assessment instrument using Quizizz PaperMode for IPAS learning on natural resources is highly feasible and practical to be used in teaching and learning activities at the elementary school level.